Adenoma papilar cístico de tireoide em cão (canis familiaris) - Dos Santos, Ivan Felismino Charas [UNESP]; Cardoso, José Manuel Mota; Brombini, Giovanna Cristina [UNESP]; Del Poente, Maira Duarte (My University, 2013)
The thyroid adenomas are not common in dogs, and the majority of cases are identified at necropsy as an accidental finding. These neoplasias affect dogs with age between 11 and 13 years old. The aim of this work was to report the surgical treatment, with no association to any adjuvant treatment, of non functional thyroid papillary cist adenoma with 8 cm in length and 6 cm in width, in a dog, Labrador breed, with four years old, attended at the Veterinary Hospital School, Mozambique. The complementary exams as image (X-ray and ultrasound), complete blood count, serum biochemistry, hormonal dosage and fine-needle aspiration (FNA), were not conclusive for the diagnosis. However, the histopathology exam was crucial for the definitive diagnosis, and the treatment by complete surgical resection, without association with chemotherapy, was effective in this case.
Thyroid papillary cist adenoma in dog (Canis familiaris)
Keywords: Cist; Endocrine gland; Neoplasia; Surgery